Value without fetish : Uno Kōzō's theory of 'pure capitalism' in light of Marx's critique of political economy - Lange, Elena Louisa (Historical materialism book series,, 2021)
"Value Without Fetish presents the first in-depth English-language study of the influential Japanese economist Uno Kōzō's (1897-1977) theory of 'pure capitalism' in the light of the method and object of Marx's Critique of Political Economy. A close analysis of the theories of value, production/reproduction, and crisis in Uno's central texts from the 1930s to the 1970s reveals his departure from Marx's central insights about the fetish character of the capitalist mode of production -- a departure that Lange shows can be traced back to the failed epistemology of value developed in Uno's earliest writings. By disavowing the complex relation between value and fetish that structures Marx's critique, Uno adopts the paradigms of neoclassical theories to present an apology rather than a critique of capitalism"--